2012
DOI: 10.1111/j.1476-5381.2012.02050.x
|View full text |Cite
|
Sign up to set email alerts
|

Cannabidiol inhibits angiogenesis by multiple mechanisms

Abstract: BACKGROUND AND PURPOSE Several studies have demonstrated anti‐proliferative and pro‐apoptotic actions of cannabinoids on various tumours, together with their anti‐angiogenic properties. The non‐psychoactive cannabinoid cannabidiol (CBD) effectively inhibits the growth of different types of tumours in vitro and in vivo and down‐regulates some pro‐angiogenic signals produced by glioma cells. As its anti‐angiogenic properties have not been thoroughly investigated to date, and given its very favourable pharmacolog… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

6
101
2
2

Year Published

2013
2013
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 140 publications
(111 citation statements)
references
References 88 publications
(99 reference statements)
6
101
2
2
Order By: Relevance
“…Furthermore, this group significantly reduced angiogenesis in vivo in Matrigel sponges. Key down-stream targets inhibited by CBD in HUVEC cells included MMP-2 and −9, TIMP1, plasminogen activator uPA, chemokines CXCL16 and IL-8, and growth factors enodothelin-1 and platelet derived growth factor-AA (Solinas et al, 2012). Moreover, CBD treatment led to a decrease in CD31 (vascularization marker) staining in tumor stroma in a mouse xenograft model where tumors were derived from subcutaneously implanted human lung cancer cells (Ramer et al, 2013).…”
Section: Non-psychoactive Plant-derived Cannabinoids As Inhibitorsmentioning
confidence: 99%
“…Furthermore, this group significantly reduced angiogenesis in vivo in Matrigel sponges. Key down-stream targets inhibited by CBD in HUVEC cells included MMP-2 and −9, TIMP1, plasminogen activator uPA, chemokines CXCL16 and IL-8, and growth factors enodothelin-1 and platelet derived growth factor-AA (Solinas et al, 2012). Moreover, CBD treatment led to a decrease in CD31 (vascularization marker) staining in tumor stroma in a mouse xenograft model where tumors were derived from subcutaneously implanted human lung cancer cells (Ramer et al, 2013).…”
Section: Non-psychoactive Plant-derived Cannabinoids As Inhibitorsmentioning
confidence: 99%
“…These vary with each cannabinoid but generally include the induction of apoptosis and/or autophagy via engagement of the mitogen-activated protein kinase (MAPK) and the endoplasmic reticulum stress-related pathways (5,7). Cannabinoids have also been reported to be antiangiogenic (8) as well as anti-inflammatory (9). Furthermore, limited clinical trial data have reinforced the concept that THC possesses therapeutic potential.…”
Section: Introductionmentioning
confidence: 99%
“…The understanding of the epigenetic regulation of keratinocyte differentiation by phytocannabinoids may pave the way to the development of new drugs for skin diseases, analogous to other human disorders like multiple sclerosis (Rog, 2010), bowel disease (Lal et al, 2011) and cancer (Solinas et al, 2012).…”
Section: Introductionmentioning
confidence: 99%
“…However, the therapeutic potential of cannabinoid-based preparations for skin diseases has not yet been investigated. Up to now, just one study has reported the inhibition of human keratinocyte proliferation by phytocannabinoids, suggesting that phytocannabinoids could be beneficial in the treatment of psoriasis (Wilkinson and Williamson, 2007).In this study, we investigated the effects of three major non-psychoactive components of Cannabis sativa (Izzo et al, 2009): CBD and its precursor cannabigerol (CBG), that are, together with Δ9-tetrahydrocannbinol, the most abundant phytocannabinoids (Hill et al, 2012b); and cannabidivarin (CBDV), a propyl analogue of CBD which like its congener has anticonvulsant properties (Jones et al, 2010;Hill et al, 2012a).The understanding of the epigenetic regulation of keratinocyte differentiation by phytocannabinoids may pave the way to the development of new drugs for skin diseases, analogous to other human disorders like multiple sclerosis (Rog, 2010), bowel disease (Lal et al, 2011) and cancer (Solinas et al, 2012). …”
mentioning
confidence: 99%